The kindness cure : how the science of compassion can heal your heart & your world - Cousineau, Tara (New Harbinger Publications, Inc., 2018)
Psychologist Tara Cousineau draws on cutting-edge research in psychology and neuroscience to show how compassion and empathy are hardwired into our DNA and essential to our survival. This book teaches effective skills in compassion, mindfulness, and social and emotional learning, and reveals successful social policy initiatives in empathy taking place that inform everything from family life to education to the workplace.